CORRELATION OF FLEXIBILITY AND BALANCE WITH MA WASHI GERY AT KARATEKA DOJO INKAI RED MARKET, MEDAN IN 2020 - Magaraja, Agustinus; Situmeang, Rahman (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This study aims to determine the correlation of flexibility and balance to the Mawashi Gery kick in Karate martial arts. The population in this study were all 13 karateka Dojo Inkai Pasar Merah Medan in 2020. The number of samples of 9 people was obtained by using purposive sampling technique, in which male athletes were used as samples. The instruments used in this study were instruments for measuring flexibility, balanced and kicking mawashi gery instruments.The results of the analysis of hypothesis I show a correlation coefficient of 0.754, which has a strong correlation. The coefficient of determination of 56.8% explains that flexibilty gives an effect of 56.8% on the mawashi geri kick while 43.2% is influenced by other variables. Based on the results of the t-test, it is known that taitung> trabei where (-3.04> -l, 86) so it can be concluded that there is a significant correlation of flexibility to the maegery kick at the 2020 Medan Red Market Inkai Dojo Karateka. The result of hypothesis II analysis shows that the correlation coefficient is 0.243, which is a weak correlation. The determination coefficient of 0.59% explains that balance has an effect of 5.9% on the mawashi geri kick while 94.1% is influenced by other variables. Based on the results of the t-test it is known that tcount <tTabei where (0.66 <l, 86) so it can be concluded that there is no significant correlation of balance to maegery kicks at the 2020 Medan Red Market Inkai Dojo karateka. The result of hypothesis III analysis shows that the correlation coefficient is 0.780, which is a strong correlation. The determination coefficient of 60.8% explains that flexibility and balance have an effect of 60.8% on the Mawashi Geri kick while 39.2% is influenced by other variables. The amount of Fcount = 4.68 while Ftabei = 4.46. In the hypothesis testing criteria it is stated that F count> F table at (4.68> 4.46). So it can be concluded that there is a significant correlation of flexibility and balance to the Mawashi Gery kick at the 2020 Medan Red Market Inkai Dojo.